The Gaia-ESO Public Spectroscopic Survey - Gilmore, G.; Randich, S.; Asplund, M.; Binney, J.; Bonifacio, P.; Drew, J.; Feltzing, S.; Ferguson, A.; Jeffries, R.; Micela, G.; Negueruela, I.; Prusti, T.; et al. (2012)
The Gaia-ESO Public Spectroscopic Survey has begun and will obtain high quality spectroscopy of some 100000 Milky Way stars, in the field and in open clusters, down to magnitude 19, systematically covering all the major components of the Milky Way. This survey will provide the first homogeneous overview of the distributions of kinematics and chemical element abundances in the Galaxy. The motivation, organisation and implementation of the Gaia-ESO Survey are described, emphasising the complementarity with the ESA Gaia mission. Spectra from the very first observing run of the survey are presented.